2012
DOI: 10.1038/ng.2413
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent somatic TET2 mutations in normal elderly individuals with clonal hematopoiesis

Abstract: Aging is characterized by clonal expansion of myeloid-biased hematopoietic stem cells and by an increased risk of myeloid malignancies. Exome sequencing of 3 elderly females with clonal hematopoiesis demonstrated by X-inactivation analysis identified somatic TET2 mutations. Recurrence testing found TET2 mutations in 10 out of 182 individuals with X-inactivation skewing. TET2 mutations were specific to individuals with clonal hematopoiesis without hematologic malignancies and were associated with alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
558
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(601 citation statements)
references
References 13 publications
16
558
1
10
Order By: Relevance
“…Such variants are typically present in a proportion of peripheral blood cells at a specific time-point but their frequency can increase or decrease over time and even disappear, suggesting a dynamic pattern of clonal change 1 . Consistent with this data, mutations in genes that are often mutated in myeloid malignancy such as TET2, DNMT3A, ASXL1 and JAK2 have also been described in elderly individuals with no evidence of hematological malignancy [5][6][7][8] . Increasing age is accompanied by changes to the hematopoietic stem cell (HSC) compartment, a process known as myeloid shift, with a bias towards the myeloid lineage at the expense of the lymphoid lineage 9 .…”
Section: Detection Of Leukemia-associated Mutations In Peripheral Blosupporting
confidence: 75%
“…Such variants are typically present in a proportion of peripheral blood cells at a specific time-point but their frequency can increase or decrease over time and even disappear, suggesting a dynamic pattern of clonal change 1 . Consistent with this data, mutations in genes that are often mutated in myeloid malignancy such as TET2, DNMT3A, ASXL1 and JAK2 have also been described in elderly individuals with no evidence of hematological malignancy [5][6][7][8] . Increasing age is accompanied by changes to the hematopoietic stem cell (HSC) compartment, a process known as myeloid shift, with a bias towards the myeloid lineage at the expense of the lymphoid lineage 9 .…”
Section: Detection Of Leukemia-associated Mutations In Peripheral Blosupporting
confidence: 75%
“…Both muta tions and deletions of the TET2 gene have been frequently observed in patients, with mutations occurring in 13% and deletions in approximately 3% [27,44,45]. A recent finding has shed more light on the function of TET2, where somatic mutations were found in normal elderly individuals pre senting with clonal hematopoiesis [50]. This discovery, alongside the mouse studies, supports the notion that TET2 enhances self renewal and clonal expansion in stem cells.…”
Section: Epigenetic Factor Mutationssupporting
confidence: 62%
“…19,20,43,44 Busque et al reported TET2 mutations in PNMs (not in lymphoid cells) from 10 of 182 (5.6%) elderly women (.65 years old) with NRXI, but not in 95 younger women (,60 years old) or 105 elderly women without NRXI. 71 More comprehensive surveys of leukemia/ MDS-associated mutations in the general population were conducted by repurposing WES data of peripheral blood DNA from large population-based studies. Jaiswal et al focused on 160 candidate mutational targets reported in hematologic cancers and found mutations in 73 genes in 746 of 17 182 participants.…”
Section: Age-related Ch In the General Populationmentioning
confidence: 99%